Understanding of the concept of Mudarabah and its application among the staff of Sekolah Kebangsaan Kampong Tengah, Manir - Abu Bakar, Rubiah; Wan Ahmad, Wan Helmy Shahriman; Mohd Fauzi, Nur Ainina; Mohd Nazri, Farah Nur Ain (Journal of Islamic, Social, Economics and Development, 2026)
This study was conducted to find out the understanding of the concept of Murabahah and its application among the staff of Sekolah Kebangsaan Kampong Tengah, Manir. Murabahah is a specific type of transaction where the seller states clearly the cost of the good being sold that he has incurred and then sells it to another person while adding a profit or markup thereon. Murabahah allows for the mutual determination of the profit, which may be expressed as a single payment or as a predetermined percentage to be charged over the costs. This study used 51 staff members of Sekolah Kebangsaan Kampong Tengah, Manir who completed an online form to answer the questionnaire of this study. Quantitative methods were used in the research methodology. Analysis of percentage, frequency, mean, and standard deviation was performed using descriptive statistics. The results of the study show that the staff of Sekolah Kebangsaan Kampong Tengah, Manir have a good understanding of Murabahah and use it in their daily lives. The findings of the study show that each variable's mean value is at a high level; the mean value of part A is 4.37, part B is 4.35, and part C is 4.47 (high). In addition, this study also aimed at assisting in expanding the understanding the concept of Murabahah and expanding the use of Islamic banking products among the community.